1996
DOI: 10.1017/cbo9780511665479
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Dynamics

Abstract: Constrained motion is of paramount importance in the design and analysis of mechanical systems and central to the study of analytical dynamics. The problem of constrained motion was first posed over two hundred years ago, and it has been worked on vigorously ever since. This book offers a fresh approach to the subject. Eminently readable, it is written as an introduction to analytical dynamics, with emphasis on fundamental concepts in mechanics. The connection between generalized inverses of matrices and cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
357
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 395 publications
(358 citation statements)
references
References 0 publications
1
357
0
Order By: Relevance
“…This control-law is especially interesting as it has a clear physical interpretation (Udwadia and Kalaba 1996;Bruyninckx and Khatib 2000;Udwadia 2003): the metric used is consistent with principle of virtual work of d'Alembert. Similarly as before we can compensate for coriolis, centrifugal and gravitational forces in joint-space, i.e., setting u 1 = C + G + u 0 .…”
Section: Dynamically Consistent Decouplingmentioning
confidence: 93%
See 4 more Smart Citations
“…This control-law is especially interesting as it has a clear physical interpretation (Udwadia and Kalaba 1996;Bruyninckx and Khatib 2000;Udwadia 2003): the metric used is consistent with principle of virtual work of d'Alembert. Similarly as before we can compensate for coriolis, centrifugal and gravitational forces in joint-space, i.e., setting u 1 = C + G + u 0 .…”
Section: Dynamically Consistent Decouplingmentioning
confidence: 93%
“…The solution to this point-wise optimal control problem (Spo 1984;Spong et al 1986) can be derived from a generalization of Gauss' principle, as originally suggested in (Udwadia 2003). It is also a generalization of the propositions in (Udwadia and Kalaba 1996;Bruyninckx and Khatib 2000). We formalize this idea in the following proposition.…”
Section: Optimal Control Frameworkmentioning
confidence: 99%
See 3 more Smart Citations